Trade policy uncertainty effects on macro economy and financial markets: An integrated survey and empirical investigation - Nikolaos A. Kyriazis (Journal of Risk and Financial Management, 2021)
This paper conducts a review on theoretical and empirical findings on the increasingly popular measure of trade policy uncertainty (TPU) in economics and finance. Moreover, an empirical investigation takes place in order to find the impact that TPU exerts on Bitcoin market values by employing a spectrum of Generalized Autoregressive Conditional Heteroskedasticity (GARCH) specifications. Existing studies support that trade policy uncertainty leads to lower-quality and more expensive products and weak participation in international trade. Moreover, it contributes to lower democratic sentiment, hesitant internal migration and lesser socio-economic mobility and higher fluctuations in profitable assets. Moreover, our econometric findings reveal that TPU positively affects Bitcoin prices while crude oil values negatively influence this major cryptocurrency. Thereby, higher trade policy uncertainty is found to increase demand and favorite investments into risky assets in order to ameliorate the risk-return trade-off in investors' portfolios. This study provides a compass for investing during turmoil due to trade wars and tariffs.
Keywords: 330; trade policy uncertainty; survey; macro economy; financial markets; Bitcoin